Needs Analysis To Design a Set of English Teaching Materials for Non-English Subject Teachers - Sri Lestari (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2020)
This article aims at describing the rationale and principles of designing English teaching materials for teachers of non-English subjects. Those teachers use English as a medium of instruction. English is used to teach the subjects. To improve the teachers’ English skills, the school provided an English course. However, the teaching materials for those specific learners were not available. Therefore, designing materials is needed to precisely fulfil their needs of English in the target professional workplace. A needs analysis was conducted to gather information using questionnaires distributed to the non-English subject teachers as the learners. The data from the questionnaire were analysed qualitatively by interpreting and categorising in themes. Using the needs analysis result, a syllabus was then designed as the guidelines for developing the materials. This paper reports how the needs analysis process is employed to design a set of English teaching materials for nonEnglish subject teachers. The discussion highlighted the present situation, the target situation, the principles of designing English materials. The overview of the designed materials for teachers of non-English subjects was then presented.